PENGARUH KUALITAS LAYANAN DAN INFORMASI INSTAGRAM TERHADAP KEPUASAN PENGUNJUNG PERPUSTAKAAN DAN KEARSIPAN KABUPATEN TEGAL - Deswa Fairysa Zahra; Sarwo Edy; Ike Desi Florina (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2026)
This study is motivated by the importance of improving the quality of services and information dissemination via Instagram to meet the needs of library visitors, as well as the gap between the services provided and visitor satisfaction levels. This study aims to analyze the influence of service quality and Instagram information on the satisfaction of library visitors in Tegal Regency. This study uses a quantitative approach to test the relationship between variabels. The study population consisted of 5,045 people, with a sample size of 98 respondents, determined using the Solvin formula at a 10% error rate. Data collection was conducted through the direct distribution of questionnaires to library visitors using a Likert scale as the measurement tool. Data analysis was performed using multiple linear regression with the assistance of SPSS version 22 software. Prior to analysis, instrument validation tests including validity, reliability, and classical assumption tests were conducted to ensure the model’s suitability. The results of the study indicate that the quality of service and information on Instagram have a positive and significant effect on visitor satisfaction simultaneously. This suggests that the better the quality of service provided and the more optimal the delivery of information via Instagram, the higher the level of visitor satisfaction. A coefficient of determination of 52.1% indicates that both independent variabels contribute. Keywords: Instagram information, satisfaction of library, service quality.